At home with guests – discussing hosting on airbnb through the lens of labour. Issue 1 (2nd January 2020) - Knaus, Katharina
ABSTRACT: Hosting Airbnb guests in the private home has become an increasingly popular activity in the past years – especially in the urban sphere. Whereas researchers have widely acknowledged that urban tourist geographies and itineraries are shifting, little attention has been paid to how Airbnb hosts provide and navigate their own homes in the platformed tourist economy. Airbnb's main claim is that one can find home and belong anywhere. But how is home actually provided by hosts and how may this effect their practices of dwelling? Taking labour as an entry point, the article will discuss how the "Airbnb home" is managed and what skills hosting presupposes. It thereby draws on empirical work conducted with Airbnb hosts in New York City who regularly rent out a room or part of their home to Airbnb guests. Considering the host perspective triggers questions of how home in the age of Airbnb may be understood and what it means to dwell with mobility.